Who is asking: Student
its substitution method i am having alot of trouble figuring it out. send the answer as soon as possible. thank you
I see two reasonable choices here.
Solve the first equation for y.
3x + y -3x = 11 - 3x
y = 11 - 3x
Substitute into the second equation.
x + 2(11 - 3x) = -3
x + 22 - 6x = -3
-5x = -25
x = 5
Finally substitute x = 5 into either of the equations you started with to find y.
Now try it the other way. Solve the second equation for x and substitute into the first equation. You should find the same answer.Cheers,